Synthesis, Characterization and Antibacterial Studies of Some Transition Metal Complexes Containing New Dithiocarbamate Ligand - Ahmed Thabitnuman Dhuha (Journal of Global Pharma Technology, 2018)
The synthesis of some transition metal complexes with dithiocarbamate as a ligand of general formula [M (L) 2] where M = Mn (II), Co (II) and Ni (II). The dithiocarbamate ligand and its complexes were described by FT-IR, UV-Vis and 1H, 13C-NMR, Mass spectra, elemental micro analysis C.H.N.S., magnetic susceptibility, molar conductivity, melting points, and atomic absorption. The antibacterial Studies of synthesized compounds were studied versus [Escherichia coli (gram negative) and Staphylococcus aureus (gram positive)]. The conductivity data affirm the nonelectrolyte nature of the complexes.Keywords: Dithiocarbamate (Dtc), 4-aminophenazone, Transition metal.